Advances in radiotherapy technology for pediatric cancer patients and roles of medical physicists: COG and SIOP Europe perspectives. (5th April 2021) - Hua, Chia‐ho; Mascia, Anthony E.; Seravalli, Enrica; Lomax, Antony J.; Seiersen, Klaus; Ulin, Kenneth
Abstract: Over the last two decades, rapid technological advances have dramatically changed radiation delivery to children with cancer, enabling improved normal‐tissue sparing. This article describes recent advances in photon and proton therapy technologies, image‐guided patient positioning, motion management, and adaptive therapy that are relevant to pediatric cancer patients. For medical physicists who are at the forefront of realizing the promise of technology, challenges remain with respect to ensuring patient safety as new technologies are implemented with increasing treatment complexity. The contributions of medical physicists to meeting these challenges in daily practice, in the conduct of clinical trials, and in pediatric oncology cooperative groups are highlighted. Representing the perspective of the physics committees of the Children's Oncology Group (COG) and the European Society for Paediatric Oncology (SIOP Europe), this paper provides recommendations regarding the safe delivery of pediatric radiotherapy. Emerging innovations are highlighted to encourage pediatric applications with a view to maximizing the therapeutic ratio.